Rearing of Milkfish, Chanos Chanos, in Net Cages at Sea at Various Stocking Densities - Sumawidjaja, Kusman; Yusdiana, T.; Effendi, Irzal; Dharmadi, , (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTStocking rate of milkfish, Chanos chanos, from 75 to 225 fish/m3 or from 1,33 to 3,98 kg/m3 did not affect the growth rate, survival rate, feeding efficiency, and final length and weight of fish, each at 2,32%/day, 81,8%, 63,8%, and 185,2 mm and 64,0 g respectively. Final biomass (Y) increased from 3,66 to 12,05 kg/m3 with the increase of stocking rate (X) with Y = 0,056 X-0,45 (p<0,05).Key words : Milkfish, Chanos chanos, floating net cage, stocking density. ABSTRAKPadat penebaran ikan bandeng, Chanos chanos, dari 75 hingga 225 ekor/m3 atau dari 1,33 hingga 3,98 kg/m3 tidak mempengaruhi laju pertumbuhan, kelangsungan hidup, efisiensi pemberian pakan serta panjang dan bobot ikan akhir, masing-masing dengan rata-rata 2,32%/hari, 81,8%, 63,8%, 185,2 mm dan 64,0 g. Biomasa akhir (Y) meningkat dari 3,66 hingga 12,05 kg/m3 dengan meningkatnya padat penebaran (X) dengan persamaan Y = 0,056 X -0,45 (p<0,05).Kata kunci : Ikan bandeng, Chanos chanos, keramba jaring apung, padat penebaran